1993
DOI: 10.1016/s0022-5347(17)35922-0
|View full text |Cite
|
Sign up to set email alerts
|

The Neurosurgical Implications of Continuous Neurourological Surveillance of Children with Myelodysplasia

Abstract: Between 1979 and 1990, 148 newborns with myelodysplasia were followed with serial urodynamic studies and neurological assessment. Of the patients 59 (40%) exhibited changes in neurological status by age 5 years, of whom 28 (19%) showed signs of deterioration. Most changes occurred before age 2 years. A total of 22 children underwent repeat neurosurgical exploration because of a change in urethral sphincter innervation (17), deterioration of function of the lower extremities (3), or changes on computerized tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…Indeed, although these criteria may reflect genuine neurogenic dysfunction, they may also represent functional disorders or be part of the normal maturation process of voiding. [10][11][12]18,24,34,38 Urologically, patients were clinically stabilized or improved in 64% of the cases in our study. This is in agreement with recommendations found in current literature, which suggest that early untethering prevents bladder deterioration and the occurrence of neurological deficits and orthopedic deformities at a later age.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Indeed, although these criteria may reflect genuine neurogenic dysfunction, they may also represent functional disorders or be part of the normal maturation process of voiding. [10][11][12]18,24,34,38 Urologically, patients were clinically stabilized or improved in 64% of the cases in our study. This is in agreement with recommendations found in current literature, which suggest that early untethering prevents bladder deterioration and the occurrence of neurological deficits and orthopedic deformities at a later age.…”
Section: Discussionsupporting
confidence: 53%
“…7,13,22,32,45 This apparent discrepancy is easily explained by the fact that our Group 1 population was younger that the ones reported in these studies. 6,8,14,18,19,22,24,35 In addition, untethering is believed by some to prevent the possibility of sudden neurourological deterioration following trivial spinal trauma. In fact, in two papers in which the age of patients with occult spinal dysraphism was specifically addressed, urological symptoms were either absent or rare in patients younger than 1.5 years, whereas findings of urodynamic studies proved abnormal in 36% and 58% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Lais et al followed 148 children with myelomeningocele and 40% showed evidence of deterioration during the first two years of life when growth is at its most rapid 24. Some studies of “occult” spinal defects are misleading, in that they suggest a significant chance of stability and even improvement in some cases 6…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that supports the fact that patients with primary tethered cord will sooner or later develop or experience worsening of neurological deficits if they do not undergo spinal cord untethering [5,6,7,8,9]. Better postoperative outcomes have been reported when this condition is repaired promptly after the appearance of deficits [10,11,12,13]. Early detection of individuals who are at risk of further deterioration is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%